Japan Administered Account for Selected IMF Activities (JSA) : Annual Report for Fiscal Year 2007. (International Monetary Fund, 2007)
This paper presents a description of the IMF and its activities, focusing in particular on its technical assistance (TA) activities. The report then describes in greater detail the Japan Administered Account for Selected Fund Activities (JSA)-including its objectives, size, scope, and use, as well as assessments of its activities, with a focus on fiscal year (FY) 2007-and the TA activities and scholarship programs that it finances. The IMF's technical assistance is delivered mainly by its Fiscal Affairs Department (FAD), Monetary and Capital Markets Department (MCM), and Statistics Department (STA). Japan provides grant contributions for two scholarship programs. In 1996, the Japan-IMF Scholarship Program for Advanced Studies, which is administered by the IMF Institute, was established. JSA resources can be used to cover the cost of short- and long-term TA experts and other costs associated with conducting seminars and workshops, such as room rental fees. Although TA activities financed by the JSA can take place in all areas of the world, the Japanese authorities place high priority on funding TA activities in Asia and the Pacific, Central Asia, Central and Eastern Europe, and countries of the former Soviet Union.